Budapest nephrology school – 30 years of history – from modest start to an international success: systematic summary of the 27th BNS held between 28th August and 2nd of September 2023 - Orsolya Cseprekál; Laszlo Rosivall (Renal Failure)
Budapest Nephrology School (BNS) could have celebrated its 30th event if it had not been interrupted by COVID pandemic for a few years. Yet, the organization of 27th BNS in August 2023 resumed its successful and traditional activities at Semmelweis University, in the beautiful central European city of Budapest. In over two decades, BNS has faithfully adapted to the changes and developments of medical science and clinical nephrology, the fact which has kept it unique and attractive for nephrologists from across the globe. With such a long history and representing the top international professors of nephrology, BNS has proved to be a successful one-week, in-person refreshing course which has attracted over 1600 medical doctors from more than 60 countries. It has well served as an academic meeting point suitable for networking and exchange of up-to-date knowledge presented by the best international experts in nephrology. The dedication and focus of these experts on education, research and patient care represent the very concept of translational medicine. The invaluable experience of the past 27 years has set the standards for BNS to contribute to the evolution of translational nephrology in Europe in the next decade.